Pengaruh Citra Merek dan Kualitas Layanan terhadap Keputusan Pembelian Mixue Cabang Cilincing Jakarta - Yuliyani, Leli; Arizona, Anisa (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This research phenomenon is because Mixue is not included in the category of the 5 most consumed contemporary beverage brands by Indonesian people in 2022. This study aims to determine and analyzethe influence of brand image and service quality on purchasing decisions Mixue Cilincing Jakarta branch. The research method used isa quantitative method with data retrieval techniques in the form of questionnaires. Sample selection in this study is the Mixue Cilincing Branch consumers who have tried ice cream Mixue minimum 1x purchase. The sampling technique used in this study is non probability sampling and using The Theory Of Hair et al so that the sample taken as many as 165 respondents. Data analysis techniques used are validitytest, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination analysis and hypothesis testing using spss software version 26. The results of this study indicate that there is a simultaneous influence on the variables of brand image and service quality on purchasing decisions. In the determination test for brand image variables there is an influence of 61.4% on purchasing decisions and the remaining 38.6% are influenced by other variablesthat are not studied. For service quality variables, there is an influenceof 66.0% on purchasing decisions and the remaining 34.0% are influenced by other variables that are not studied. While there is an influence of 70.3% which is explained by the variables of brand image and service quality on purchasing decisions and the remaining 29.7% which is influenced by other variables not studied.